2020
DOI: 10.1158/1078-0432.ccr-19-2485
|View full text |Cite
|
Sign up to set email alerts
|

PI3K Inhibitors Curtail MYC-Dependent Mutant p53 Gain-of-Function in Head and Neck Squamous Cell Carcinoma

Abstract: TRANSLATIONAL RELEVANCEHead and neck squamous cell carcinoma (HNSCC) is typically characterized by mutation of TP53 gene, associated to therapy resistance and high incidence of local recurrences. However, drugs specifically targeting mutant p53 proteins, frequently presenting gain-of-function activity associated with radioresistance, are not available. We then set out to identify mutant p53-associated functions that might be targeted with drugs currently used in HNSCC trials. This study identifies MYC as a cru… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 58 publications
2
54
3
Order By: Relevance
“…Indeed, we found that depletion of mutant p53 proteins in HNSCC cell lines increased TMPRSS2 expression, suggesting that mutant p53 contributes either directly or indirectly to reduced TMPRSS2 expression. Unlike depletion of mutant p53, silencing of YAP and MYC, two oncogenic co-factors of gain of function mutant p53 proteins did not have any effect of TMPRSS2 expression [22,29,30]. While these ndings may entirely rule out a possibility that gain of function mutant p53-dependent transcriptional networks controls TMPRSS2 expression in HNSCC cells, our observations highlight that tumor cells carrying TP53 mutations may activate post-transcriptional events affecting TMPRSS2 expression.…”
Section: Discussioncontrasting
confidence: 52%
See 3 more Smart Citations
“…Indeed, we found that depletion of mutant p53 proteins in HNSCC cell lines increased TMPRSS2 expression, suggesting that mutant p53 contributes either directly or indirectly to reduced TMPRSS2 expression. Unlike depletion of mutant p53, silencing of YAP and MYC, two oncogenic co-factors of gain of function mutant p53 proteins did not have any effect of TMPRSS2 expression [22,29,30]. While these ndings may entirely rule out a possibility that gain of function mutant p53-dependent transcriptional networks controls TMPRSS2 expression in HNSCC cells, our observations highlight that tumor cells carrying TP53 mutations may activate post-transcriptional events affecting TMPRSS2 expression.…”
Section: Discussioncontrasting
confidence: 52%
“…Notably, we found that reduced expression of TMPRSS2 associates with HPV negative status and TP53 mutations, both of which are important determinants of poor survival in HNSCC patients. We have recently shown that MYC as oncogenic protein di per se and a MYC-dependent gene signature cooperate with gain of function TP53 mutations to foster HNSCC proliferation and to increase resistance to the treatment [22]. Indeed, we found that depletion of mutant p53 proteins in HNSCC cell lines increased TMPRSS2 expression, suggesting that mutant p53 contributes either directly or indirectly to reduced TMPRSS2 expression.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…We have recently reported that MYC is a pivotal mediator of gain of function mutant p53 signalling in HNSCC [ 24 ]. We have identified a mutantp53/MYC dependent signature whose aberrant activation (high expression levels) associated with shorter overall survival in HNSCC patients (Suppl.…”
Section: Resultsmentioning
confidence: 99%